Penentuan Hydroquinon menggunakan Metode The Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) - R. K. Sanjaya; A. Restyana; N. Ismillayli; D. Hermanto (PKimia FKIP Universitas Halu Oleo, 2021)
The reverse phase high performance liquid chromatography (HPLC) method was used to determine the hydroquinone content. Determination was carried out under the optimum conditions of the RP-HPLC method including methanol as the mobile phase, flow rate 1 mL/min, running time 5 minutes, injection volume 20 L, UV detector, wavelength 290 nm with internal standard hydroquinone. The measurement results show that the reversed-phase HPLC method is a sensitive and high-precision method with a detection limit below 0.5% w/w. The results of determining the hydroquinone content in the preparation sample in the form of cream using the reverse phase HPLC method in sample A and sample B were 2.26% and 2.32%, respectively. Statistical analysis based on the RPD value of sample A and sample B has a value of less than 10%. Therefore, the reverse phase HPLC method is expected to be an accurate method for routine analysis of hydroquinone in cosmetic samples and pharmaceutical products.